Robot‐assisted partial nephrectomy vs laparoscopic cryoablation for the small renal mass: redefining the minimally invasive 'gold standard'. (31st October 2013) - Emara, Amr M.; Kommu, Sashi S.; Hindley, Richard G.; Barber, Neil J.
Abstract : Objective: To identify differences between the ablative and extirpative minimally invasive techniques of laparoscopic cryoablation (LC) and robot‐assisted laparoscopic partial nephrectomy (RPN), respectively, in treating small renal tumours in terms of safety, peri‐operative morbidity and early oncological outcomes. Patients and Methods: Between June 2008 and April 2012 56 patients underwent LC and from October 2010 to April 2012, 47 patients underwent RPN using the Da Vinci robotic platform (Intuitive Surgical, Sunnyvale, CA, USA). Data on intra‐operative, postoperative and oncological outcomes were collected prospectively, and were analysed and compared for both groups. Results: The median patient ages were 69 and 60 for the LC and RPN groups, respectively ( P < 0.05). There was no significant difference in disease stage, but there was a significant difference in tumour size, with patients in the RPN group having larger tumours. The mean operating times were 146 and 159 min for the LC and RPN groups, respectively ( P = 0.094) and the mean blood loss was 47 and 94 mL for the LC and the RPN groups, respectively ( P = 0.251). The median length of hospital stay (1 day) was the same for both groups and the mean warm ischaemia time was 23 min in the RPN group. The marginal change in preoperative and 6‐week postoperative renal function was recorded: the mean postoperative increase in serum creatinine was 5.4 mmol/L in the LC group and 9.2 mmol/L in the RPN group. Of the 47 patients in the RPN group, two (4.3%) were converted to laparoscopic radical nephrectomy because of difficulty in controlling bleeding during hilar dissection. Only two patients (3.6%) had recurrence in the LC group, both of whom were treated with re‐cryoablation. A total of 5.4% of patients in the LC and 4.3% in the RPN group had Clavien grade I postoperative complications, one patient in the LC group had a Clavien grade II complication, while 1.8 and 4.3% of patients had Clavien IIIb in the LC and RPN groups, respectively. Conclusion: Our data confirm that LC is a successful, minimally invasive and safe treatment option for the management of small renal tumours, but the apparently similar characteristics of RPN suggest that an increasing proportion of patients, whatever their age or medical comorbidities, may be reasonably offered a robot‐assisted extirpative procedure with the likely benefit of lower risk of local recurrence and need for retreatment.